2022
DOI: 10.3390/diagnostics12112575
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Causes of Not-Detected Breast Malignancy in Dynamic Contrast-Enhanced MRI

Abstract: Breast MR is the most sensitive imaging modality, but there are cases of malignant tumors that are not detected in MR. This study evaluated the frequency and main causes of malignant breast lesions not detected in dynamic contrast-enhanced (DCE) MR. A total of 1707 cases of preoperative breast MR performed between 2020 and 2021 were included. Three radiologists individually reviewed the DCE MRs and found not-detected malignancy cases in the MRs. The final cases were decided through consensus. For the selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…Among our 4 false-negative cases, there were 2 invasive ductal carcinomas with ductal carcinoma in situ and 1 ductal carcinoma in situ. In a previous study of 1,707 cases, 12 cases were false negatives ( 27 ), with invasive ductal carcinoma accounting for 0.3% of the lesions and ductal carcinoma in situ accounting for 0.4%; moreover, the proportion of false negatives was significantly lower than that in our study. However, other studies ( 32 , 33 ) have reported false-negative rates that are consistent with our results.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Among our 4 false-negative cases, there were 2 invasive ductal carcinomas with ductal carcinoma in situ and 1 ductal carcinoma in situ. In a previous study of 1,707 cases, 12 cases were false negatives ( 27 ), with invasive ductal carcinoma accounting for 0.3% of the lesions and ductal carcinoma in situ accounting for 0.4%; moreover, the proportion of false negatives was significantly lower than that in our study. However, other studies ( 32 , 33 ) have reported false-negative rates that are consistent with our results.…”
Section: Discussioncontrasting
confidence: 84%
“…Use of the Kaiser score in this study yielded 5 false-positive cases and 4 false-negative cases. We speculate that these misdiagnoses occurred for the following reasons: (I) with high-grade BPE, the biopsy recommendation rate of breast MRI reading is higher compared with lower grades of BPE ( 27 ). Owing to the particularity of the data in this study, the inclusion criteria were moderate and marked BPE, and among the 9 false-positive and false-negative cases, 6 (85.7%) of the lesions were smaller than 10 mm in diameter, making it almost impossible to separate the lesions from the breast parenchyma ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…These changes often cause the formation of metabolites in cancer cells that can be distinguished from the metabolites of normal cells [ 14 ]. Imaging techniques such as magnetic resonance imaging (MRI) can be used to study increased metabolite uptake by tumor cells, which could translate into earlier diagnosis and improved patient outcomes [ 15 ]. Integrated bioinformatics and systems biology can play a role in understanding and testing key expressed genes related to BC recurrence.…”
mentioning
confidence: 99%
“…In the case report by Vlastarakos, the tumor measured 23 mm on breast MRI but was not detected on mammography [ 19 ]. There are few studies addressing non-enhancing ILC on MRI, which are summarized in Table 1 [ 8 , 9 , [20] , [21] , [22] ].…”
Section: Discussionmentioning
confidence: 99%